Screening and Counseling Practices Reported by Obstetrician-Gynecologists for Patients With Hepatitis C Virus Infection - Kathy Boaz; Anthony E. Fiore; Stephanie J. Schrag; Bernard Gonik; Jay Schulkin (Hindawi Limited, 2003)
Background: Obstetrician-gynecologists are important providers of primary health care to women, and the hepatitis C virus (HCV) infection screening practices and recommendations provided by obstetrician-gynecologists for HCV-infected patients are unknown.